2003
DOI: 10.1152/ajpregu.00267.2002
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of acid adaptation of a fish living in a pH 3.5 lake

Abstract: Despite unfavorable conditions, a single species of fish, Osorezan dace, lives in an extremely acidic lake (pH 3.5) in Osorezan, Aomori, Japan. Physiological studies have established that this fish is able to prevent acidification of its plasma and loss of Na(+). Here we show that these abilities are mainly attributable to the chloride cells of the gill, which are arranged in a follicular structure and contain high concentrations of Na(+)-K(+)-ATPase, carbonic anhydrase II, type 3 Na(+)/H(+) exchanger (NHE3), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
239
5
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 207 publications
(268 citation statements)
references
References 64 publications
23
239
5
1
Order By: Relevance
“…Plasma pH values between 7.3 and 7.5 have been reported to be normal values in fish (Hirata et al, 2003), which correspond well with the values found in our study. A two-day decrease of water pH was not experienced as stressful in the present study as indicated by the lack of a significant rise in plasma pH and cortisol levels, which is in line with previous reports (Ginneken et al, 1997;Lamers et al, 1994), in which either a 6h or a 24h period of gradual water acidification was applied.…”
Section: Plasma Analysis -Effects O F Water Acidificationsupporting
confidence: 92%
“…Plasma pH values between 7.3 and 7.5 have been reported to be normal values in fish (Hirata et al, 2003), which correspond well with the values found in our study. A two-day decrease of water pH was not experienced as stressful in the present study as indicated by the lack of a significant rise in plasma pH and cortisol levels, which is in line with previous reports (Ginneken et al, 1997;Lamers et al, 1994), in which either a 6h or a 24h period of gradual water acidification was applied.…”
Section: Plasma Analysis -Effects O F Water Acidificationsupporting
confidence: 92%
“…1), and the conventional NCC was not markedly expressed in the gill (Fig. 2) (11,16,54), suggesting that a NCC-independent mechanism is operating in the gills of freshwater mefugu to absorb sodium ions; one possibility involves NHE3, as previously proposed by this group, Choe et al, and Yan et al for the Osorezan dace (20), Atlantic stingray (8), and zebrafish (57), respectively. Future studies will focus on the regulatory mechanisms that govern NCC and NKCC2 gene expression and how the various nephron segments are formed.…”
Section: Perspectives and Significancesupporting
confidence: 59%
“…NBC1 has been immunocytochemically identified in gill ionocytes of Osorezan dace (Tribolodon hakonensis) (Hirata et al, 2003) and rainbow trout (Parks et al, 2007). In a study on isolated rainbow trout gill PNA -cells (Parks et al, 2007), electrogenic NBC activity was supported by DIDS (an NBC inhibitor)-sensitive, Na + -induced membrane potential depolarization as observed via imaging of the voltage-sensitive dye bis-oxonol.…”
Section: Basolateral Transport Pathwaysmentioning
confidence: 99%